A peptide-based synthetic transcription factor selectively activates transcription in a mammalian cell. Issue 13 (25th January 2018) - Roy, Koushik; Mazumder, Abhishek; Ghosh, Piya; Naiya, Gitashri; Ghosh, Basusree; Roy, Siddhartha
Abstract : A peptide-based cell permeable synthetic transcription factor is reported, which binds to its target site with high affinity and specificity. Abstract : A peptide-based cell permeable synthetic transcription factor is reported, which binds to its target site with high affinity and specificity. When linked to a HAT-binding peptide, it causes significant upregulation of gene expression in a mammalian cell. Such molecules may be developed for selectively activating repressed genes in mammalian cells.